Minimally Invasive Spine Surgery for Unstable Thoracolumbar Burst Fractures: A Case Series - Agarwal, Nitin; Choi, Phillip A.; Sekula, Raymond F. (The Surgery Journal, 2016)
Introduction Traumatic thoracolumbar burst fracture is a common pathology without a clear consensus on best treatment approach. Minimally invasive approaches are being investigated due to potential benefits in recovery time and morbidity. We examine long-term resolution of symptoms of traumatic thoracolumbar burst fractures treated with percutaneous posterior pedicle screw fixation.Methods Retrospective clinical review of seven patients with spinal trauma who presented with thoracolumbar burst fracture from July 2012 to April 2013 and were treated with percutaneous pedicle screw fixation. Electronic patient charts and radiographic imaging were reviewed for initial presentation, fracture characteristics, operative treatment, and postoperative course.Results The patients had a median age of 29 years (range 18 to 57), and 57% were men. The median Thoracolumbar Injury Classification and Severity Scale score was 4 (range 2 to 9). All patients had proper screw placement and uneventful postoperative courses given the severity of their individual traumas. Five of seven patients were reached for long-term follow-up of greater than 28 months. Six of seven patients had excellent pain control and stability at their last follow-up. One patient required revision surgery for noncatastrophic hardware failure.Conclusion Percutaneous pedicle screw fixation for the treatment of unstable thoracolumbar burst fracture may provide patients with durable benefits and warrants further investigation.
Keywords: thoracolumbar burst fracture; minimally invasive spine surgery; fusion; spine trauma